Effect of nano-SiO2 films on the electron radiation induced conductivity of polyimide - 岳龙 吴宜勇 孙承月 石亚平 肖景东 何世禹 (中国物理B：英文版, 2013)
The radiation induced conductivity （RIC） behaviors in nano-SiO2 deposited polyimide （PI） were investigated using the in situ measurement technique. The results indicate that, by comparison with the case of virgin polyimide, the RIC in nano-SiO2/polyimide shows low steady state values. Moreover, the steady state RIC is a power function of the dose rate with a power index of 0.659, lower than that of 0.76 in the virgin polyimide. The interfacial barrier and trapping effects are the main reasons for the change. Meanwhile, both of the interfacial effects also result in a unipolar carrier transportation mechanism in nano-SiO2 deposited PI from the dipolar one in the virgin PI. The mechanisms of the RIC behaviors are discussed in the paper.